2013
DOI: 10.1016/j.fertnstert.2013.01.130
|View full text |Cite
|
Sign up to set email alerts
|

Number of supernumerary vitrified blastocysts is positively correlated with implantation and live birth in single-blastocyst embryo transfers

Abstract: Objective To estimate if live birth in single blastocyst transfers is correlated with the number of sibling supernumerary vitrified blastocysts (embryos not transferred) generated from that same cycle. Design Retrospective cohort study. Setting A large academic ART clinic. Patients All single blastocyst transfers in 2010 of a SART grade ‘good’ embryo. Interventions None. Main Outcome Measures Implantation and live birth. Results 655 single blastocyst transfers met inclusion criteria. Implantation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
11
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 20 publications
8
11
0
Order By: Relevance
“…There are other variables aside from maternal age that were associated with positive outcomes. Some are intuitive and consistent with prior literature in older women, including the retrieval of more oocytes [5,9,20], the transfer of more embryos [4,6,21] at a more advanced embryonic stage, and the cryopreservation of more supernumerary embryos [22]. Similar to what has been seen previously [23], our study found that a lower gonadotropin dose was associated with higher rates of clinical pregnancy and live birth in the multivariable analysis.…”
Section: Discussionsupporting
confidence: 90%
“…There are other variables aside from maternal age that were associated with positive outcomes. Some are intuitive and consistent with prior literature in older women, including the retrieval of more oocytes [5,9,20], the transfer of more embryos [4,6,21] at a more advanced embryonic stage, and the cryopreservation of more supernumerary embryos [22]. Similar to what has been seen previously [23], our study found that a lower gonadotropin dose was associated with higher rates of clinical pregnancy and live birth in the multivariable analysis.…”
Section: Discussionsupporting
confidence: 90%
“…One study reported a statistical difference in the number of supernumerary embryos for freezing between the two randomized groups (Day 3 progesterone group: 1.3 embryos for freezing versus Day 6 progesterone group: 2.7 embryos for freezing, P =0.01) (20). Supernumerary embryos have been associated with an increased likelihood of pregnancy (24). …”
Section: Resultsmentioning
confidence: 99%
“…Our study is limited by its cycle-based rather than patient-based nature, by the lack of some patient medical information such as tobacco use, nonfertility-related medical history, obstetric complications, interpregnancy interval, pregnancy weight gain, and the lack of embryo quality data. To minimize the effects of lack data on embryo quality, we were able to control for the number of supernumerary embryos cryopreserved, which has been shown to correlate with embryo quality (27) and number of prior failed IVF cycles. Additionally, the study is limited by the quality of height and weight data entered by clinicians and by the fact that 18% of BMI data are missing.…”
Section: Discussionmentioning
confidence: 99%